Model Kualitas Layanan Produk Sepeda Motor Pada Industri Otomotif di Indonesia - Dedi - Herdiansyah; Meizi Fahrizal (Politeknik Negeri Padang, 2021)
The purpose of this study is to obtain the concept of a service quality model for motorcycle products in the automotive industry in Indonesia. Furthermore, the concept that will be formed expected to enrich the insights of interested parties in service management and opportunities for improving the implementation of service quality, especially for motorcycle product manufacturers in the automotive industry in Indonesia, which can then be used as a tool to compete. fellow manufacturers of motorcycle products in Indonesia. This study uses a descriptive qualitative research approach, with the method of collecting data through in-depth interviews. After the interview, transcription was carried out and continued with the data analysis. From the analysis of the data, the research found several themes of service quality dimensions, consist of: (a). Technical quality namely technology, (b). Functional quality, namely safety, security, comfort and convenience. The main functional quality from the user's perspective is security. Based on the results of the study, these dimensions are the focus of services that must be provided by motorcycle manufacturers, as a tool to compete with other motorcycle manufacturers. Key words: Service Quality Model, Features on Motorcycle and User Perspective